Effect of hyperosmotic stress on hemolymph protein, muscle ninhydrin-positive substances and free amino acids in Macrobrachium rosenbergii (de man) - Tan, C. H.; Choong, K. Y. (Elsevier, 1981)
1. Acclimation of M. rosenberqii by gradual transfer from dilute to more concentrated media caused a significant decrease in the hemolymph protein content.